Pulmonary artery sling in preschool patient with airway compromise (2019)
Background: Left pulmonary artery sling is a rare congenital malformation of the aortic arch in which this artery originates from the right pulmonary artery and courses over the trachea and the esophagus. Clinical manifestations vary depending on the degree of airway compromise, the esophagus and associated cardiac anomalies. The treatment for this malformation is surgical; over the years, this approach has improved, achieving a decrease in morbidity and mortality in this condition. Case report: A preschool patient with incidental finding of sling of the left pulmonary artery with compromise of the airway is presented. Conclusions: After the surgical procedure, a favorable clinical outcome was observed and a significant improvement in the airway was shown by a fibrobronchoscopy, without any additional intervention. © 2019, Publicaciones Permanyer. All rights reserved.